Evaluation of Management Strategy in Increasing the Competitiveness of MSMEs at the Cooperative and MSME Service - Sri Indah Ayu Permata Sari; M. Ikhsan Harahap; Tri Inda Fadhila Rahma (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) IAI Al Urwatul Wutsqo - Jombang, 2025)
To analyze the management strategies implemented by the Cooperatives and SMEs Office of Batu Bara Regency in improving the competitiveness of Micro, Small, and Medium Enterprises (MSMEs). This study also aims to examine three main aspects of management strategies: marketing strategies, financial strategies, and human resources (HR) strategies, to determine the effectiveness of their implementation in supporting the development of MSMEs in the region. The methodology used in this study is a qualitative approach with descriptive methods. The types of evidence used in this study include primary and secondary data. Primary data were obtained through in-depth interviews and direct observation of employees of the Cooperatives and SMEs Office of Batu Bara Regency and assisted MSMEs, while secondary data came from office documents, activity reports, and literature related to MSME development policies. All data were analyzed descriptively through the stages of data reduction, data presentation, and drawing conclusions to obtain a comprehensive picture of the management strategies implemented in improving the competitiveness of MSMEs. The findings indicate that the marketing strategy focuses on digital marketing training but lacks ongoing mentoring. The financial strategy facilitates business legality and access to financing, but faces structural and literacy barriers. Human resource training improves technical skills but remains inconsistent. Overall, management strategies are not fully aligned with the needs of MSMEs.